Peran Kearifan Lokal Suku Sasak di Era Disrupsi dalam Menangkal Perilaku Menyimpang pada Kalangan Siswa di MAN 1 Lombok Timur - Siti Surodiana (Universitas Pendidikan Mandalika, 2020)
This study aims to: 1) describe the forms of deviant behavior in the era of disruption; 2) describe the forms of local wisdom of Sasak tribe that can ward off deviant behavior among MAN 1 students in East Lombok. This research method uses a descriptive qualitative approach. Data collection techniques in this study are observation, interviews, and documentation. The results of this study show that the form of deviant behavior found in students is often late to go to school, Anti Social (prefer to be alone rather than hanging out with peers), Students spend a lot of time with social media, Students work on assignments given by the teacher by copying faste someone else's work, Skipping class hours, Saying Rude / impolite, Lying to parents to buy a quota on the grounds of looking for material but used to play online games, Cheating during exams using cellphones, Having an attitude of indifference (Indifferent not Indifferent), bullying peers through social media. While the form of local wisdom that can suppress deviant behavior can be in the form of awiq-awiq, lelakaq, and folklore. Meanwhile the role of local wisdom of Sasak tribe community in counteracting deviant behavior in MAN 1 East Lombok is by applying local wisdom in sociology learning and early in the morning before the KBM schedule begins by waiting students with the greetings and greetings tradition.